Dark fall - Andrews, Brian, 1973-; Wilson, Jeffrey, 1963- (Andrews, Brian, 1973- Shepherds series, 2022)
"When a remote Peruvian village is reduced to ash in seconds, the Shepherds face a horrific question: Is this the work of a man-made weapon of unthinkable power, or is God raining down judgment from above, as some believe? As the recently installed leader of the Joshua Bravo team, Jedidiah Johnson shifts into covert operation mode to follow rumors of a new energy-based weapon able to incinerate a target--even a human target--with no warning. With the assistance of the CIA, Jed's team deploys to Hong Kong to extract the Chinese scientist who helped develop the weapon. What the Shepherds learn from Dr. Zhao confirms their worst fears: The weapon is real and has disappeared from the testing facility where it was held. With help from the Watchers, Jed discovers that Victor, the leader of the Dark Ones, has the weapon and intends to use it to wreak untold damage and destabilize the faith of millions. But as Jed and his team race the clock to find and disable the weapon, Victor begins to unfold secret plans for another attack... And this target is much closer to home."--Amazon.com.